Identification and Fine Mapping of RppM, a Southern Corn Rust Resistance Gene in Maize - Wang, Shuai; Zhang, Ruyang; Shi, Zi; Zhao, Yanxin; Su, Aiguo; Wang, Yuandong; Xing, Jinfeng; Ge, Jianrong; Li, Chunhui; Wang, Xiaqing; Wang, Jidong; Sun, Xuan; et al. (Frontiers in Plant Science, 2020)
Southern corn rust (SCR) caused by Puccinia polysora Underw. is a major disease causing severe yield losses during maize production. Here, we identified and mapped the SCR resisitance gene RppM from the near-isogenic line Kangxiujing2416 (Jing2416K), which harbors RppM in the genetic background of the susceptible inbred line Jing2416. In this study, the inheritance of SCR resistance was investigated in F2 and F3 populations derived from a cross between Jing2416K and Jing2416. The observed 3:1 segregation ratio of resistant to susceptible plants indicated that the SCR resistance is controlled by a single dominant gene. Using an F2 population, we performed bulked segregant analysis (BSA) sequencing and mapped RppM to a 3.69-Mb region on chromosome arm 10S. To further narrow down the region harboring RppM, we developed 13 insertion/deletion (InDel) markers based on the sequencing data. Finally, RppM was mapped to a region spanning 110-kb using susceptible individuals from a large F2 population. Two genes (Zm00001d023265 and Zm00001d023267) encoding putative CC-NBS-LRR (coiled-coiled, nucleotide-binding site and leucine-rich repeat) proteins, a common characteristic of R genes, were located in this region (B73 RefGen_v4 reference genome). Sequencing and comparison of the two genes cloned from Jing2416K and Jing2416 revealed sequence variations in their coding regions. The relative expression levels of these two genes in Jing2416K were found to be significantly higher than those in Jing2416. Zm00001d023265 and Zm00001d023267 are thus potential RppM candidates.